2022
DOI: 10.1371/journal.pgph.0001177
|View full text |Cite
|
Sign up to set email alerts
|

The scenario of knowledge, attitude and practice of the Bangladeshi population towards thalassemia prevention: A nationwide study

Abstract: Thalassemia is one of the most common life-threatening yet preventable congenital hemoglobin disorders especially in South Asian regions like Bangladesh. It has become a rising public health concern for Bangladesh as 6–12% of the population are carriers and many of them are unaware of it. The purpose of the study is to inspect the knowledge and attitude towards thalassemia among the general people of Bangladesh. A cross-sectional survey was conducted in eight administrative regions of Bangladesh between Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
11
1
Order By: Relevance
“…The findings of this study support the reports from other locations in Bangladesh. A nationwide survey of 1248 people revealed about half the participants was rightly informed about thalassemia and its risk factors, while 72.5% were aware of pre-marital blood test for Thalassemia screening, 68.2% were in favor of premarital screening and 85.3% were compassionate enough to donate blood for existing Thalassemic patients (N. E. Alam et al, 2022). The study by revealed the urban-rural divide and prejudice against Thalassemic patients among college students.…”
Section: Discussionmentioning
confidence: 97%
“…The findings of this study support the reports from other locations in Bangladesh. A nationwide survey of 1248 people revealed about half the participants was rightly informed about thalassemia and its risk factors, while 72.5% were aware of pre-marital blood test for Thalassemia screening, 68.2% were in favor of premarital screening and 85.3% were compassionate enough to donate blood for existing Thalassemic patients (N. E. Alam et al, 2022). The study by revealed the urban-rural divide and prejudice against Thalassemic patients among college students.…”
Section: Discussionmentioning
confidence: 97%
“…In a study done among college students in Bangladesh, 88% of them reported a positive perception of premarital screening 5 . In another study which was done in Bangladesh, 68.2% exposed a positive attitude towards premarital testing 13 . Therefore, more health education programs should be conducted in view of sociocultural factors among college students because of their positive attitude towards premarital screening.…”
Section: Premarital and Genetic Screeningmentioning
confidence: 99%
“…While advancements in blood transfusion and iron chelation therapies have improved the quality of life for individuals with thalassemia, they are far from curative. 1,2 Various methods have been studied as potential alternatives for treating thalassemia, with gene therapy being one of them. Gene therapy has emerged as a promising solution for various diseases, including thalassemia, due to its capacity to address the genetic roots of the condition.…”
Section: Introductionmentioning
confidence: 99%
“…Thalassemia, a group of inherited blood disorders characterized by defective hemoglobin (Hb) production, remains a significant global health concern, particularly in regions with a high prevalence of consanguineous marriages. While advancements in blood transfusion and iron chelation therapies have improved the quality of life for individuals with thalassemia, they are far from curative 1,2 . Various methods have been studied as potential alternatives for treating thalassemia, with gene therapy being one of them.…”
Section: Introductionmentioning
confidence: 99%